Genocídio Armênio: contribuições jurídicas ao aprimoramento do Direito Internacional dos Direitos Humanos - Furtado, Nathália Hovsepian de Souza (2024)
The aime of the presente researche is the study of the Armenian genocide from the perspective of International Human Rights Law and human rights education, to answer the central question: what is the contribution of the Armenian genocide to the prevention and repression of the crime of genocide? Divided into three parts, this research will analyze in detail the Armenian genocide of 1915 and its historical context, followed by the study of the legal consequences of the crime and finally, by the analysis of the case of Artsakh (2022/2023) and its possible classification as a crime of genocide, which could constitute a second Armenian genocide. The Armenian genocide of 1915 presents itself as a little studied topic of great historical and legal relevance. By shedding light on the topic, we seek historical reparation for the victims by recognizing the Armenian genocide as a crime, as well as contributing to the prevention of new crimes of this kind, through human rights education. The work will also analyze the direct and indirect legal contribution of the crime to the improvement of International Human Rights Law. With emphasis on the universalization of the protection of minorities, the creation of the concepts of genocide and crimes against humanity, the conception of the idea of holding States and individuals responsible for genocidal practice, as well as the conception and development of the International Criminal Court. The main legal documents on the subject will be analyzed, with emphasis on the London Agreement in 1945, which established the Nuremberg Tribunal; UN General Resolution 96, of December 11, 1946; the 1948 Convention for the Prevention and Suppression of the Crime of Genocide; Resolution 827 of 1993, of the UN Security Council, which creates the International Criminal Tribunal for the former Yugoslavia; Resolution 955 of 1994, of the UN Security Council, which creates the International Criminal Tribunal for Rwanda; and the 1998 Rome Statute, which creates the International Criminal Court. Finally, the case of Artsakh in 2023 will be analyzed, when the Armenian population of the Nagorno/Karabakh region was subjected to nine months of siege by Azerbaijan, followed by a bellicose invasion and the massive deportation of almost the entire population of the area. The presentation of the case aims to analyze and discuss the main advances in the field and promote the discussion of new directions in the prevention of genocide